FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN PELAYANAN ANTENATAL CARE DI BPM PERMATA BUNDA SLOGOHIMO WONOGIRI - Kristiningtyas, Y. Wahyunti; Triwahyuniastuti, Triwahyuniastuti (Akademi Keperawatan Giri Satria Husada Wonogiri, 2019)
Antenatal screening is an important part of antenatal care shaping the way services are delivered. In accordance with the role of a midwife as stipulated in the Regulation of the Minister of Health of the Republic of Indonesia number 28 / MENKES / PER / X / 2017 concerning the license and implementation of midwife practice which includes maternal health services, child health services and women's reproductive health services and family planning. Antenatal care aims to prevent complications and ensure that complications in childbirth can be detected early and treated properly. Antenatal examinations are an important part of antenatal care shaping the way services are delivered. Routine initial visits at least nine examinations which include: weighing, measuring blood pressure, nutritional status (measure upper arm circumference), measuring fundal height, determining fetal presentation and Fetal Heart Rate (FHR), giving complete tetanus toxoid immunization, giving iron tablets of at least 90 tablets, tests for sexually transmitted diseases (STDs) and talks in preparation for referrals (Sullivan. A, Kean. L and Cryer. A, 2009). According to the data obtained, the ANC visit at BPM Permata Bunda is classified as higher than at the surrounding BPM. At BPM Permata Bunda in 1 year in 2018 there were 754 visits by pregnant women. This is because the services provided by midwives are very satisfying and the check rates are very affordable. The purpose of this study is to describe the factors that affect the utilization of ANC services at BPM Permata Bunda, Waru Slogohimo Village in 2018. The sample in this study were all pregnant women who examined at BPM Permata Bunda in Waru Village, Slogohimo as many as 62 people and the sample was taken by way of accidental sampling. The research design used was descriptive with a cross-sectional approach. This study uses a questionnaire instrument that has been tested for validity and reliability. The results showed that (1) the characteristics of the respondents were: 66.1% of respondents were 20-35 years old, 14.5% of respondents were <20 years old and 19.4% of respondents were> 35 years old. The factors that influence the utilization of ANC services are knowledgeable (53.2%), have graduated from junior high school (38.7%), the decision makers are done by themselves (51.6%). Based on the distance traveled, respondents said that the distance was close (53.2%). Based on economic status, respondents have low income (56.4%). Then based on the actions taken by the midwife, respondents said that the actions taken by the midwife were good or according to standards (96.8%).